Evaluation of the CGIAR Research Program on Wheat - Beversdorf, Wallace; Brouder, Sylvie; Sachdeva, Paramjit; Sulaiman, Rasheed; Templeton, Deborah (CGIAR Independent Evaluation Arrangement, 2015)
The CGIAR Research Program on WHEAT (WHEAT) (http://wheat.org/) is led by CIMMYT and operated in partnership with ICARDA and other partners. WHEAT aims at increasing the productivity of wheat farming systems in order to serve the 2.5 billion poor consumers for whom wheat is a staple food, and to bring benefits to wheat producers and enhance the sustainability of wheat systems.